2010
DOI: 10.1111/j.1365-2141.2010.08377.x
|View full text |Cite
|
Sign up to set email alerts
|

Autologous 111In‐labelled platelet sequestration studies in patients with primary immune thrombocytopenia (ITP) prior to splenectomy: a report from the United Kingdom ITP Registry

Abstract: SummaryWhile splenectomy is an effective therapy for primary immune thrombocytopenia (ITP), possible complications and observed noncomplete response (CR) in one-third of patients demonstrate the need for further research into potential pre-surgical predictors of outcomes. Past investigations into platelet sequestration studies, a hypothesized predictive test, have adopted heterogeneous methods and varied widely with regard to power. By studying patients with primary ITP who underwent autologous 111 In-labelled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
1
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 30 publications
1
63
1
3
Order By: Relevance
“…In this regard, other prognostic parameters should be explored before splenectomy, particularly radio-labeled platelet scans. 23,24 The analysis of the 95 patients (41%) who did not achieve a stable response showed that, despite most of them needing multiple lines of further treatments, a new response was achieved in 83% of the cases, confirming that splenectomy can convert refractory patients into responding ones, and does not exclude the possibility of a second response in relapsing patients. 19,20 Indeed, only 16 patients (7%) did not respond to any further treatment and only 3 (1%) died of bleeding complications.…”
Section: Discussionmentioning
confidence: 96%
“…In this regard, other prognostic parameters should be explored before splenectomy, particularly radio-labeled platelet scans. 23,24 The analysis of the 95 patients (41%) who did not achieve a stable response showed that, despite most of them needing multiple lines of further treatments, a new response was achieved in 83% of the cases, confirming that splenectomy can convert refractory patients into responding ones, and does not exclude the possibility of a second response in relapsing patients. 19,20 Indeed, only 16 patients (7%) did not respond to any further treatment and only 3 (1%) died of bleeding complications.…”
Section: Discussionmentioning
confidence: 96%
“…However, conflicting results have been reported regarding the value of this complementary investigation to predict splenectomy outcome. 18,19 Future studies focusing on the predictive value of platelet-longevity scintigraphy may help determine better whether a patient could benefit from romiplostim before undergoing splenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Sarpatwari et al [24] applied the S/L ratio described by Najean et al [34] in 72 patients after splenectomy. Between 6 and 12 month postsurgery a CR was observed in 87.0% of the patients with a purely or predominantly splenic destruction pattern and only in 27.8% of the patients with a mixed or hepatic destruction pattern.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there was a significant consensus in considering that the scintigraphic proof of the spleen as the main site of platelet destruction was the most valuable parameter for predicting a favorable outcome of splenectomy. Different scintigraphic indices have been proposed for this evaluation, such as spleen/liver [15,[22][23][24], spleen/heart [14] and spleen/spleen [13,25] at different times after the injection of autologous 111…”
Section: Introductionmentioning
confidence: 99%